Protocol to evaluate fasting metabolism and its relationship to the core circadian clock in mice - Jiameng Sun; Brian J. DeBosch (STAR Protocols)
Summary: To investigate the role of hepatocyte genes in fasting metabolism, it is essential to analyze their expression across the entire 24-h circadian cycle. Here, we present a protocol to evaluate fasting metabolism and its relationship to the core circadian clock in mice. We describe steps for time-course fasting/feeding experiment setup and performing staggered fasting and refeeding for 24 h. We then detail procedures for evaluating oxidative substrate selection and rescuing defective oxidative metabolism through FGF21 and CPI-613 injections.For complete details on the use and execution of this protocol, please refer to Sun et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.